Identification of marine natural product Pretrichodermamide B as a STAT3 inhibitor for efficient anticancer therapy - Rui Li; Yue Zhou; Xinxin Zhang; Lujia Yang; Jieyu Liu; Samantha M. Wightman; Ling Lv; Zhiqing Liu; Chang-Yun Wang; Chenyang Zhao (Marine Life Science & Technology, 2023)
The Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) regulates the expression of various critical mediators of cancer and is considered as one of the central communication nodes in cell growth and survival. Marine natural products (MNP) represent great resources for discovery of bioactive lead compounds, especially anti-cancer agents. Through the medium-throughput screening of our in-house MNP library, Pretrichodermamide B, an epidithiodiketopiperazine, was identified as a JAK/STAT3 signaling inhibitor. Further studies identified that Pretrichodermamide B directly binds to STAT3, preventing phosphorylation and thus inhibiting JAK/STAT3 signaling. Moreover, it suppressed cancer cell growth, in vitro, at low micromolar concentrations and demonstrated efficacy in vivo by decreasing tumor growth in a xenograft mouse model. In addition, it was shown that Pretrichodermamide B was able to induce cell cycle arrest and promote cell apoptosis. This study demonstrated that Pretrichodermamide B is a novel STAT3 inhibitor, which should be considered for further exploration as a promising anti-cancer therapy.

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)